Mapování telomerázové aktivity a telomerické sekvence u brouků - Prušáková, Daniela (Jihočeská univerzita, 2020)
(TTAGG)n sequence is an ancestral common telomere motif in insects, yet not ubiquitous, especially in beetle lineage, where the structure of telomeres varies even between representatives of the same clade. Telomerase activity related to the ancestral sequence was examined using TRAP assay, occurence of (TTAGG)n and (TCAGG)n repeats across beetles was determined using hybridization methods.
Mapping of telomerase activity and telomeric sequence in beetles
Keywords: telomeres; telomerase; beetles